Sustained Expression of Negative Regulators of Myelination Protects Schwann Cells from Dysmyelination in a Charcot–Marie–Tooth 1B Mouse Model - Florio, Francesca (J Neurosci, 2018)
Schwann cell differentiation and myelination in the PNS are the result of fine-tuning of positive and negative transcriptional regulators. As myelination starts, negative regulators are downregulated, whereas positive ones are upregulated. Fully differentiated Schwann cells maintain an extraordinary plasticity and can transdifferentiate into “repair” Schwann cells after nerve injury. Reactivation of negative regulators of myelination is essential to generate repair Schwann cells. Negative regulators have also been implicated in demyelinating neuropathies, although their role in disease remains elusive. Here, we used a mouse model of Charcot–Marie–Tooth neuropathy type 1B (CMT1B), the P0S63del mouse characterized by ER stress and the activation of the unfolded protein response, to show that adult Schwann cells are in a partial differentiation state because they overexpress transcription factors that are normally expressed only before myelination. We provide evidence that two of these factors, Sox2 and Id2, act as negative regulators of myelination in vivo. However, their sustained expression in neuropathy is protective because ablation of Sox2 or/and Id2 from S63del mice of both sexes results in worsening of the dysmyelinating phenotype. This is accompanied by increased levels of mutant P0 expression and exacerbation of ER stress, suggesting that limited differentiation may represent a novel adaptive mechanism through which Schwann cells counter the toxic effect of a mutant terminal differentiation protein. SIGNIFICANCE STATEMENT In many neuropathies, Schwann cells express high levels of early differentiation genes, but the significance of these altered expression remained unclear. Because many of these factors may act as negative regulators of myelination, it was suggested that their misexpression could contribute to dysmyelination. Here, we show that the transcription factors Sox2 and Id2 act as negative regulators of myelination in vivo, but that their sustained expression in Charcot–Marie–Tooth type 1B (CMT1B) represents an adaptive response activated by the Schwann cells to reduce mutant protein toxicity and prevent demyelination.